Introducing segmentation cracks in air plasma‐sprayed thermal barrier coatings by controlling residual stress. Issue 2 (17th September 2021) - Luo, Lirong; Zou, Zhonghua; Shan, Xiao; Cai, Huangyue; Yang, Lixia; Jin, Hongyun; Zhao, Xiaofeng
Abstract: Segmentation cracks are crucial for enhancing the strain tolerance and decreasing the propensity of delamination for thermal barrier coatings (TBCs). In this study, segmentation cracks were prepared in air plasma‐sprayed TBCs by controlling the residual stress. The evolution of the stress in the coating was characterized via photoluminescence piezospectroscopy using trace α ‐Al2 O3 impurities as stress sensor. Tensile stress (~170 MPa) formed in the as‐deposited coating was converted into compressive stress through further thermal exposure. The relationship between the formation of the segmentation cracks and stress in the coating was investigated. It was demonstrated that the segmentation cracks could be formed when a critical coating thickness is achieved. The critical coating thickness and spacing of the segmentation cracks dependent on the tensile stress in the as‐deposited coating, and they could be manipulated by controlling the deposition and substrate temperatures. In addition, the evolution of the microstructure and phase composition of the yttria‐stabilized zirconia coating was examined.